2007
DOI: 10.1038/sj.jid.5700760
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Dynactin p150Glued Subunit for the Functional Integrity of the Keratinocyte Microparasol

Abstract: The keratinocyte microparasol, composed of a perinuclear microtubular/melano-phagolysosomal complex, protects the nucleus from UV-induced DNA damage. We have previously demonstrated that cytoplasmic dynein is the motor involved in the perinuclear-directed aggregation of phagocytosed melanosomes. Dynactin, of which p150(Glued) is the major subunit, can link directly to microtubules and links organelles to dynein at different domains. To further define the mechanism of the microparasol, we transfected siRNA targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…10,29 Second, synthetic fluorescent microspheres had been used to establish the role of the dynactin p150Glued subunit as a required part of the cellular machinery for keratinocytes in which the knockout showed a lack of microparasol formation. 30 To test our hypothesis, we first synthesized spherical MelNPs by spontaneous oxidization of dopamine under alkaline conditions, introducing aqueous ammonium hydroxide to an aqueous solution of monomers (Figure 1). 31 The resulting spherical MelNPs showed a narrow size distribution around 200 nm, observed by transmission electron microscopy (TEM) (Figure 1a), scanning electron microscopy (SEM) (Figure 1b) and dynamic light scattering (DLS) (Figure S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,29 Second, synthetic fluorescent microspheres had been used to establish the role of the dynactin p150Glued subunit as a required part of the cellular machinery for keratinocytes in which the knockout showed a lack of microparasol formation. 30 To test our hypothesis, we first synthesized spherical MelNPs by spontaneous oxidization of dopamine under alkaline conditions, introducing aqueous ammonium hydroxide to an aqueous solution of monomers (Figure 1). 31 The resulting spherical MelNPs showed a narrow size distribution around 200 nm, observed by transmission electron microscopy (TEM) (Figure 1a), scanning electron microscopy (SEM) (Figure 1b) and dynamic light scattering (DLS) (Figure S1).…”
mentioning
confidence: 99%
“…This suggests that the transport process may be dependent on particle type, and that polydopamine nanoparticle surface chemistry plays a role in governing cellular distribution patterns. 30 …”
mentioning
confidence: 99%
“…The same study also reported that treatment with anti-sense DNA for cytoplasmic dynein heavy chain leads to a significant dispersion of perinuclear melanin in human keratinocytes. Subsequent studies demonstrated that the silencing of the dynactin p150 Glued subunit impairs the perinuclear clustering of microspheres in human keratinocytes [122], which suggests that melanin polar-ization is dependent on the cytoplasmatic dynein-dynactin motor complex (Figure 5). These results were further corroborated by recent studies, which reported a significant impairment in melanin polarization upon disruption of the actin cytoskeleton and the microtubule network [123].…”
Section: Melanin Polarizationmentioning
confidence: 99%
“…Subsequently, the melanocores are internalized by keratinocytes through phagocytosis, which relies on the activation of protease-activated receptor-2 (PAR-2) (Wu and Hammer, 2014;Tadokoro and Takahashi, 2017;Moreiras et al, 2022). Following the transfer of melanin to keratinocytes, the cytoplasmic intermediate protein chains of dynein (Dync1i1) link the entire motor complex and the p150 Glued (DCTN1) subunit of the dynactin complex, which regulates the localization of perinuclear melanin (Byers et al, 2003;Byers et al, 2007). The calcium-dependent G protein-coupled and Akt signaling pathways upregulate the expression of DCTN1 in keratinocytes after exposure to UVA radiation.…”
Section: Melanin Transfer To Keratinocytesmentioning
confidence: 99%